Mechanical and petrophysical analysis of synthetic sandstone for enhanced oil recovery applications - Costa, S. E. D. (2021)
The present work aims to develop a methodology for the preparation of synthetic sandstone to be used in enhanced oil recovery (EOR) studies. It also analyzes synthetic sandstone’s properties. A 2³ factorial planning with central point in triplicate was performed, evaluating parameters such as concentration of ceramic clay, compaction pressure and sintering temperature through porosity, permeability, and uniaxial compression strength. The sandstone produced presented porosity and permeability similar to those found in natural rocks, which make them suitable for use in EOR research